Who teaches medical billing? A national cross-sectional survey of Australian medical education stakeholders. Issue 7 (16th July 2018) - Faux, Margaret; Wardle, Jonathan; Thompson-Butel, Angelica G; Adams, Jon
Abstract : Importance: Billing errors and healthcare fraud have been described by the WHO as 'the last great unreduced health-care cost'. Estimates suggest that 7% of global health expenditure (US487 billion) is wasted from this phenomenon. Irrespective of different payment models, challenges exist at the interface of medical billing and medical practice across the globe. Medical billing education has been cited as an effective preventative strategy, with targeted education saving A250 million in Australia in 1 year from an estimated A1–3 billion of waste. Objective: This study attempts to systematically map all avenues of medical practitioner education on medical billing in Australia and explores the perceptions of medical education stakeholders on this topic. Design: National cross-sectional survey between April 2014 and June 2015. No patient or public involvement. Data analysis—descriptive statistics via frequency distributions. Participants: All stakeholders who educate medical practitioners regarding clinical practice (n=66). 86% responded. Results: There is little medical billing education occurring in Australia. The majority of stakeholders (70%, n=40) did not offer/have never offered a medical billing course. 89% thought medical billing should be taught, including 30% (n=17) who were already teaching it. There was no consensus on when medical billing education should occur. Conclusions: To our knowledge, this is the first attempt of any country to map the ways doctors learn the complex legal and administrative infrastructure in which they work. Consistent with US findings, Australian doctors may not have expected legal and administrative literacy. Rather than reliance on ad hoc training, development of an Australian medical billing curriculum should be encouraged to improve compliance, expedite judicial processes and reduce waste. In the absence of adequate education, disciplinary bodies in all countries must consider pleas of ignorance by doctors under investigation, where appropriate, for incorrect medical billing.